Peningkatan Improving Operational Efficiency Through Innovation and Human Resource Development: Peningkatan Efisiensi Operasional Melalui Inovasi dan Pengembangan Sumber Daya Manusia - Indah Rizqi Tsania; Ira Cahyanti; Talitha Salsabila; Sri Rohimah; Herlinda Maya Kumala Sari (Procedia of Social Sciences and Humanities, 2026)
General Background Modern business units must continuously optimize internal management processes to maintain competitiveness in dynamic markets. Specific Background Retail business operations face challenges in balancing work flexibility, cross-departmental coordination, and employee competency development. Knowledge Gap How informal internal coaching and workforce rotation interact to optimize daily operational efficiency remains under-explored in field-based management studies. Aims This study examines the role of innovation and human resource development in improving operational efficiency within a commercial business unit. Results Field observations and managerial interviews reveal that operational efficiency improves through product-category promotions, structured work rotation, shift scheduling, and weekly performance reviews. Novelty The findings demonstrate an operational framework connecting informal field-based mentoring with cross-unit coordination to overcome technical skill limitations. Implications Businesses can strengthen operational resilience by combining flexible workforce allocation with structured internal skill development. Key Findings Highlights Differentiated promotion strategies and structured shift scheduling streamline daily business unit workflow. Job rotation combined with informal field mentoring improves employee adaptability and service quality. Weekly performance evaluations against key indicators enable prompt operational adjustments and problem resolution. Keywords: Operational Efficiency, Human Resource Development, Organizational Innovation, Workforce Rotation, Business Performance